Instrumentation and Measurement Technologies for Water Cycle Management - Di Mauro, Anna.; Scozzari, Andrea; Soldovieri, Francesco (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book aims at presenting a unified framework for the description of working principles, recent advances and applications of cutting-edge measurement technologies for the water sector. Instrumentation and measurement technologies are currently playing a key role in the monitoring, assessment and protection of environmental resources. Measurement techniques and sensing methods for the observation of water systems are rapidly evolving and are requiring an increased multi-disciplinary participation. The whole water sector is characterised by multiple technological contexts concerning the monitoring of the resource, given the broad coverage that includes water from its natural domains to the men-made infrastructures. In particular, instrumentation and measurement technologies have a pervasive presence in all the necessary aspects for the assessment, monitoring and control of the water resource and of its relationship with the various environmental stressors, including the anthropic pressures. Therefore, the book aims at presenting how the diagnostics/monitoring methodologies and the related technologies can give an answer to the issues raised by the complex scenario characterising the water cycle management (WCM). The book is structured in five topical sections, grouped by similarity of their technological and/or applicative contexts.
Regional Adaptation of Water Quality Algorithms for Monitoring Inland Waters: Case Study from Irish Lakes -- Optical remote sensing in Lake Trasimeno: understanding from applications across diverse temporal, spectral and spatial scales -- Satellite instrumentation and technique for oil pollution monitoring of the seas -- Satellite instrumentation and technique for monitoring of seawater quality -- Inland Water altimetry: technological progress and applications -- Generic Strategy for Consistency Validation of the Satellite-, In-situ-, and Reanalysis - based Climate Data Records (CDRs) Essential Climate Variables (ECVs) -- Optical spectroscopy for on line water monitoring -- Fiber optic technology for environmental monitoring: state of the art and application in the Observatory of transfers in the Vadose Zone- (O-ZNS) -- Plants, vital players in the terrestrial water cycle -- Improving water quality and security with advanced sensors and indirect water sensing methods.
Keywords: Water; Hydrology; Environmental management; Natural disasters; Refuse and refuse disposal; Water; Environmental Management; Natural Hazards; Waste Management/Waste Technology